2006
DOI: 10.1299/jsmeb.49.434
|View full text |Cite
|
Sign up to set email alerts
|

Measurement on the Fluid Forces Induced by Rotor-Stator Interaction in a Centrifugal Pump

Abstract: The pressure fluctuations and the radial fluid forces induced by rotor-stator interaction in a centrifugal pump were measured and their relationship was investigated. Experiments were done for various guide vanes, flow rates, and rotating speeds. It was demonstrated that both the blade pressure fluctuations and the volute static pressures are non-uniform circumferentially (not axisymmetric) under off-design operating conditions and that the two have a strong relationship. At high flow rates, the interaction-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…When blade trailing edge flap is located in pressure side of impeller as shown in Figures 14 and 15, the pressure fluctuation grows. Because the fluid excitation force depends on pressure fluctuation [12], the shaft vibration increases when the pressure fluctuation enlarges. Therefore, the small pressure fluctuation leads to the shaft vibration decreasing.…”
Section: Influence Of Blade Trailing Edge Flap On Shaft Vibrationmentioning
confidence: 99%
“…When blade trailing edge flap is located in pressure side of impeller as shown in Figures 14 and 15, the pressure fluctuation grows. Because the fluid excitation force depends on pressure fluctuation [12], the shaft vibration increases when the pressure fluctuation enlarges. Therefore, the small pressure fluctuation leads to the shaft vibration decreasing.…”
Section: Influence Of Blade Trailing Edge Flap On Shaft Vibrationmentioning
confidence: 99%
“…Additionally, pressure fluctuations at the blade passing frequency revealed that the blade tongue interacted with the flow at the impeller outlet plane, and the interaction had clear effects, such as increased fluctuation levels under off-design conditions, limited operation ranges, and increased losses. Guo et al [6] measured pressure fluctuations and the radial fluid forces induced by the rotor-stator interaction and investigated their relationship, and they demonstrated that both the blade pressure fluctuations and the volute static pressures were circumferentially nonuniform (not axisymmetric) under off-design operating conditions. Rodriguez et al [7] carried out a theoretical analysis to qualitatively predict and explain the moving blade passing frequency and the relationship between their amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…For the mixed-flow pump, Hao et al [15] studied the effects of tip clearance size and symmetry on the radial fluid force. With respect to the geometry of diffuser, Guo et al [16,17] carried out an experimental study on the pressure pulsation and radial fluid force of a centrifugal pump with a varying number of diffuser vanes. For the mixed-flow RCP mentioned before, Ni et al [18] studied the effect of diffuser vane trailing edge profile on the pressure pulsation.…”
Section: Introductionmentioning
confidence: 99%